Gestión de recursos humanos en el comercial favorito parroquia San Juan - Terranova Rocha, Mirian Anabel (2022)
The fundamental pillar of any commercial organization is its employees, known as internal customers and the intellectual capital of an organization; their basic function is to provide the external customer with a personalized, special, quality and efficient service. They are the face and connectors of the service they offer; and they serve as intermediaries between what is sold and the services they provide to external customers. At the national level there is a great demand in the purchase and sale of mass consumption products, whether they are personal or basic necessities, but for there to be good sales in the market, it is necessary that the staff of El Favorito be trained and motivated to provide a better service. The training and motivational courses given to the employees are essential for the good quality and efficiency of the business sales. That is why the objective of this research is to generate innovative communication strategies to create motivational campaigns, which are a contribution to the growth of human talent within the commercial Favorito.